JADIKAN DIRI GURU INSPIRATIF MELALUI LESSON STUDY - Handayani, Baiq Sri (Jurnal PIJAR, 2012)
Abstrak: Sosok guru yang mampu bertahan dalam menghadapi tantangan dan perubahan paradigma pendidikan adalah guru inspiratif. Guru inspiratif merupakan guru yang melahirkan daya tarik dan spirit perubahan terhadap diri siswa serta mampu mendisain pembelajaran yang inspiratif. Kriteria guru inspiratif minimal mempunyai tiga kompetensi yaitu: kompetensi profesional, komptensi sosial dan kompetensi personal. Lesson study (LS) merupakan suatu pembinaan profesi pendidik melalui pengkajian pembelajaran secara kolaboratif dan berkelanjutan berdasarkan prinsip kolegalitas. Mengkaji pembelajaran secara kolaboratif dalam kegiatan LS dapat memberikan makna yang sangat berarti bagi guru dalam meningkatkan kompetensi guru sehingga terbentuk guru inspiratif yang dapat meningkatkan hasil belajar siswa serta memberikan inspirasi bagi sesama guru dan siswa. Tulisan ini merupakan kajian terhadap implementasi lesson study sebagai salah satu cara membentuk guru inspiratif. Dengan harapan bahawa guru termotivasi untuk menjadikan diri mereka guru inspiratif melalui kegiatan lesson study. Kata kunci: Guru Inspiratif, Lesson Study Abstract: A teacher who is able to survive in the face of challenge and change the paradigm of education is inspiring teacher. Inspiring teacher is a teacher who gave birth to the attraction and the spirit of the changes to the student and to be able to design an inspiring learning. Criteria inspiring teacher has a minimum of three competencies: professional competency, social competency and personal competence. Lesson study (LS) is a professional educator development through assessment and ongoing collaborative learning based on the principle of collegiality. Assessing collaborative learning in LS activity can provide a very significant meaning for the teachers to improve the competence of teachers to form the inspiring teacher to improve student learning outcomes and provide inspiration for fellow teachers and students. This paper is a review of the implementation of lesson study as a way to form an inspiring teacher. With the hope that free teachers themselves are motivated to make inspiring teachers through lesson study. Key Words: Inspiring teacher, lesson study